The contribution of French patient and consumer groups to health technology assessments over a 2-year period: an observational retrospective study. (22nd March 2021) - Gesbert, Cedric; André-Vert, Joëlle; Guerrier, Marc; Galbraith, Margaret; Devaud, Christine; Dupont, Jean-Claude K.; Mamzer, Marie-France
Abstract: Background: In 2017, The French National Authority for Health (HAS) created an open, online, systematic contribution process to enable patient and consumer groups (PCGs) to contribute to health technology assessment (HTA) carried out to aid public authorities in reimbursement and pricing decision making. Objectives: This retrospective study analyzes how French PCGs contributed to the HTA process within the HAS for the first 2 years of this new mechanism. Methods: PCG contributions received between 01 January 2017 and 31 December 2018 and the recording of deliberations leading to reports of the corresponding HTAs were included. Analysis grids were designed by the investigators with 5 rounds of refinement tests on 10 random PCG contributions and the reports. Systematic data extraction was then performed separately by two investigators. PCG answers to the open-question templates and the related final HTA report published by the HAS were analyzed. Results: Seventy-nine contributions from 44 PCGs were received and analyzed by the HAS for 78 out of the 592 HTAs performed for drugs or medical devices during the 2-year period. Twenty-five percent of the HTAs performed for drugs received at least one contribution. The contributions covered quality-of-life aspects, access to care, and personal and family impact. Membership and budget of the contributing PCGs varied greatly. Conclusions: The experience gained in the first 2 years demonstrates the feasibility of the process and the fact that PCG contribution actually provides relevant input on the patient perspective for HTAs used for reimbursement decisions. The challenges identified on the side of PCGs were time constraints and human resources.